SA Heart Newsletter Summer 2016 - Authors, Various (SA Heart Journal, 2017)
The executive of the South African Heart Association had decided during the course of 2015 to draft a more formal business structure for the association. The process of registering the SA Heart Association as a non-profit company (NPC) was initiated. A memorandum of incorporation, which was based on the SA Heart constitution, was drawn up. Calls for nominations and elections for board members were made and the board of directors voted in were Dr Sajidah Khan, Dr Hellmuth Weich and Dr Belinda Mitchell, aside from Prof Karen Sliwa and Prof Francis Smit who, as president and treasurer of SA Heart respectively, remain ex-officio members of the board.